Single-cell transcriptomics reveals the heterogeneity and function of mast cells in human ccRCC - Song, Xiyu; Jiao, Jianhua; Qin, Jiayang; Zhang, Wei; Qin, Weijun; Ma, Shuaijun (Frontiers in Immunology, 2025)
IntroductionThe role of mast cells (MCs) in clear cell renal carcinoma (ccRCC) is unclear, and comprehensive single-cell studies of ccRCC MCs have not yet been performed.MethodsTo investigate the heterogeneity and effects of MCs in ccRCC, we studied single-cell transcriptomes from four ccRCC patients, integrating both single-cell sequencing and bulk tissue sequencing data from online sequencing databases, followed by validation via spatial transcriptomics and multiplex immunohistochemistry (mIHC).ResultsWe identified four MC signature genes (TPSB2, TPSAB1, CPA3, and HPGDS). MC density was significantly greater in ccRCC tissues than in normal tissues, but MC activation characteristics were not significantly different between ccRCC and normal tissues. Activated and resting MCs were defined as having high and low expression of MC receptors and mediators, respectively, whereas proliferating MCs had high expression of proliferation-related genes. The overall percentage of activated MCs in ccRCC tissues did not change significantly but shifted toward a more activated subpopulation (VEGFA+ MCs), with a concomitant decrease in proliferative MCs (TNF+ MCs) and resting MCs. An analysis of the ratio of TNF+/VEGFA+ MCs in tumors revealed that MCs exerted antitumor effects on ccRCC. However, VEGFA+MC was produced in large quantities in ccRCC tissues and promoted tumor angiogenesis compared with adjacent normal tissues, which aroused our concern. In addition, MC signature genes were associated with a better prognosis in the KIRC patient cohort in the TCGA database, which is consistent with our findings. Furthermore, the highest level of IL1B expression was observed in macrophages in ccRCC samples, and spatial transcriptome analysis revealed the colocalization of VEGFA+ MCs with IL1B+ macrophages at the tumor–normal interface.DiscussionIn conclusion, this study revealed increased MC density in ccRCC. Although the proportion of activated MCs was not significantly altered in ccRCC tissues compared with normal tissues, this finding highlights a shift in the MC phenotype from CTSGhighMCs to more activated VEGFA+MCs, providing a potential therapeutic target for inhibiting ccRCC progression.